2014
DOI: 10.1093/eurpub/cku165.005
|View full text |Cite
|
Sign up to set email alerts
|

Decreasing educational differences in mortality over 40-years: evidence from the Turin Longitudinal Study (Italy)

Abstract: Background Recent studies suggest that inequalities in premature mortality have continued to rise over the last decade in most European countries, but not in southern European countries. Methods In this study, we assess long-term trends in absolute and relative educational inequalities in all-cause and cause-specific mortality in the Turin Longitudinal Study (Turin, Italy), a recordlinkage study including all individuals resident in Turin in the 1971, 1981, 1991 and 2001 censuses, and aged 30-99 years (more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In recent years, several studies in Western countries have reported secular trends in mortality inequalities 8–17. Education has been commonly used as a socioeconomic position indicator in these studies 8 10–14 16 17. Several of these studies have reported widening differences in mortality between the more and the less educated, despite overall declines in mortality rates 8 11–13 17.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, several studies in Western countries have reported secular trends in mortality inequalities 8–17. Education has been commonly used as a socioeconomic position indicator in these studies 8 10–14 16 17. Several of these studies have reported widening differences in mortality between the more and the less educated, despite overall declines in mortality rates 8 11–13 17.…”
Section: Introductionmentioning
confidence: 99%
“…When socioeconomic status was measured by social class, Costa, Zengarini, Demaria, D'Errico, and Leombruni (2013) showed that in Turin, male and female managers at age 65 had life expectancies 3 years and 1 year higher, respectively, than unskilled manual workers. Stringhini et al (2015) found that absolute educational inequality in mortality strongly declined over 40 years in Turin. Relative differences were stable among men and tended to narrow among women.…”
Section: Differential Longevity By Educational Level In Italymentioning
confidence: 98%